Karakteristik Fisikokimia dan Sensori Nori Daun Pohpohan dengan Kombinasi Pati Uwi Putih dan Karagenan - Zulfa Tiara Salsabila Rusmiadi; Ahmad Ni'matullah Al-Baarri; Anang Mohamad Legowo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Analog nori is made from ingredients other than seaweed using alternative ingredients such as green plant leaves. The innovation of using pohpohan leaves can minimize the import of Porphyra as the main ingredient of nori by the addition of starch and carrageenan as hydrocolloids can improve the nori quality. This research aimed to optimize nori's physical, chemical, and sensory properties from pohpohan leaves by the difference in yam starch ratio and carrageenan concentrations. The research used a factorial Completely Randomized Design (CRD) with a ratio of pohpohan leaves and yam starch (90:10, 80:20, 70:30, w:w) and carrageenan concentrations (2% and 3%). The results showed that the addition of yam starch and carrageenan significantly affected (p<0.05) the tensile strength, moisture content, and ash content and did not significantly affect (p>0.05) the fibre content of nori. The physicochemical quality of nori showed a tensile strength increased between 1.18-7.43 Mpa; water content decreased between 8.43-10.24%, ash content decreased between 10.14-12.96%, and crude fibre decreased between 13.63-16.85%. The sensory evaluation showed that the panellists' preference for nori taste, colour, and texture had a significant effect (p<0.05), with the highest preference value from taste 3.65, colour 4.28, and texture 4.24 on a scale of 1(dislike)-5(like). In contrast, the appearance and aroma of nori had no significant effect (p>0.05).